Quality Improvement Project to Improve the Resident Doctors’ Out-of-Hours Clinical Handover System at Nottinghamshire Healthcare NHS Foundation Trust (NHFT) - Ayodeji Akerele; Abiodun Omonori; Deepa Bagepalli Krishnan; Catherine Faruqi; Kehinde Junaid (BJPsych Open)
Aims: An effective and safe clinical handover system is at the heart of safe healthcare delivery, ensuring continuity of care between clinical teams. Handovers are completed face-to-face or verbally and recorded within the NHFT’s SharePoint handover system, the standard agreed upon within the Trust. This project aimed to improve the usability, access, and safety of a preexisting SharePoint handover system.